(untitled) (American Journal of Education and Technology, 2023)
This study examined the factors that affect the student’s performance in virtual classroom instruction and the student’s perception of virtual classroom instruction. The study used a descriptive research design to categorize the study variables, and it presents quantitative research that used internet surveys to collect data from respondents. The participants in the study were third-year BSED-English students enrolled in the second semester of the A.Y. 2020–2021 at the College of Teacher Education (CTE) of Mindoro State University, Philippines. 59 out of 90 student respondents participated in the survey in a span of three weeks, which covered 65% of the identified student respondents. The study used a researcher-made online survey questionnaire using Google forms with a close-ended statement. Results revealed that the support of the university and the support of instructors are great contributors to students’ performance in virtual classroom instruction. Meanwhile, regarding students’ perception of virtual classroom instruction, virtual classroom instruction does not meet students’ needs and learning styles and equips students’ knowledge, skills, and abilities, which affirms that students’ needs and learning styles are met when learning is face-to-face. It is necessary to provide a user-friendly Learning Management System (LMS) from a pedagogical perspective. Teachers must detect student needs and scaffold learning by closely observing student involvement and participation patterns to ensure they meet students’ needs and learning styles and equip their knowledge, skills, and abilities.